IGF1R expression by adult oligodendrocytes is not required in the steady‐state but supports neuroinflammation. Issue 3 (17th November 2022) - Locatelli, Giuseppe; Marques‐Ferreira, Filipa; Katsoulas, Antonis; Kalaitzaki, Vasileia; Krueger, Martin; Ingold‐Heppner, Barbara; Walthert, Sabrina; Sankowski, Roman; Prazeres da Costa, Olivia; Dolga, Amalia; Huber, Magdalena; Gold, Maike; et al.
Abstract: In the central nervous system (CNS), insulin‐like growth factor 1 (IGF‐1) regulates myelination by oligodendrocyte (ODC) precursor cells and shows anti‐apoptotic properties in neuronal cells in different in vitro and in vivo systems. Previous work also suggests that IGF‐1 protects ODCs from cell death and enhances remyelination in models of toxin‐induced and autoimmune demyelination. However, since evidence remains controversial, the therapeutic potential of IGF‐1 in demyelinating CNS conditions is unclear. To finally shed light on the function of IGF1‐signaling for ODCs, we deleted insulin‐like growth factor 1 receptor (IGF1R) specifically in mature ODCs of the mouse. We found that ODC survival and myelin status were unaffected by the absence of IGF1R until 15 months of age, indicating that IGF‐1 signaling does not play a major role in post‐mitotic ODCs during homeostasis. Notably, the absence of IGF1R did neither affect ODC survival nor myelin status upon cuprizone intoxication or induction of experimental autoimmune encephalomyelitis (EAE), models for toxic and autoimmune demyelination, respectively. Surprisingly, however, the absence of IGF1R from ODCs protected against clinical neuroinflammation in the EAE model. Together, our data indicate that IGF‐1 signaling is not required for the function and survival of mature ODCs in steady‐state and disease. Main Points: Absence of insulin‐like growth factor 1 receptor from mature oligodendrocytes: does not impair their survival and myelin maintenance. does not affect cuprizone‐induced toxic demyelination. ameliorates experimental autoimmune encephalomyelitis.